ANALISIS KETERLIBATAN WANITA DALAM TINDAK PIDANA PEREDARAN NARKOTIKA PADA MASA PADEMI COVID-19 - Bayu Adhitya (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
Drug trafficking remains a major threat in Indonesia amid the Covid-19 pandemic. The drug dealer that destroys the future of the Indonesian nation continues to carry out its activities, the mode of carrying out its actions is constantly being updated, in order to trick the law enforcement apparatus into carrying out crimes successfully. Drug abuse in the midst of the Covid-19 pandemic will become a new problem because the spread of Covid 19 cannot make peace with anyone, so a solution must be found. In the current pandemic situation, the National Police is not standing still, but still supervises and protects the younger generation from the dangers of drugs. It has been predicted that drug trafficking during Covid-19 will be mostly through cyberspace (online). Likewise, with the closure of entertainment venues, drugs will target from house to house. The involvement of women in narcotics networks during the Covid-19 pandemic was due to loss of jobs and income. By using the juridical normative writing method, the author tries to parse what factors cause women to participate in narcotics trafficking and what are the forms of prevention and control of narcotics circulation during the Covid-19 period. The hope is that this paper can contribute constructively to both government agencies, police and BNN